Penelusuran Hipertensi melalui Pemeriksaan Tekanan Darah pada Populasi Usia Produktif di SMAN 75, Jakarta Utara - Singh, Arwinder; Destra, Edwin; Kurniawan, Junius; Permatasari, Nabila Jingga (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2024)
Hypertension, often thought of as a condition that only affects adults, is now increasingly recognised as a significant health problem among teenagers. Hypertension is a major risk factor for morbidity and mortality from cardiovascular disease and is a public health problem throughout the world. The number of hypertension sufferers continues to increase every year; it is estimated that by 2025 there will be 1.5 billion people affected by hypertension, and it is estimated that every year 9.4 million people will die from hypertension and its complications. The goal of this community service activity, which emphasizes education and screening for high blood pressure, is to raise public awareness of the importance of maintaining normal blood pressure and detecting and preventing hypertension early. Through this community service activity, it is hoped that greater awareness will be created regarding the importance of maintaining normal blood pressure and preventing hypertension. Implementing lifestyle modifications can help to prevent hypertension and its complications, ultimately improving health outcomes and overall quality of life.